2012
DOI: 10.1007/s00484-012-0554-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an evaporative cooling system on plasma cortisol, IGF-I, and milk production in dairy cows in a tropical environment

Abstract: Access to an evaporative cooling system can increase production in dairy cows because of improved thermal comfort. This study aimed to evaluate the impact of ambient temperature on thermoregulation, plasma cortisol, insulin--like growth factor 1 (IGF--I), and productive status, and to determine the efficiency of an evaporative cooling system on physiological responses under different weather patterns. A total of 28 Holstein cows were divided into two groups, one with and the other without access to a cooling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
2
4
0
2
Order By: Relevance
“…The difference in cortisol (Table 3) was significantly (p<0.05) lower in treatment group (24.33±1.84 ng/ml) in comparison to control (33.04±0.27 ng/ml) during winter while the difference was nonsignificant in spring in both control (15.63±0.48 ng/ml) and treatment (13.90±0.38 ng/ ml) group of animals. The present study found the highest cortisol concentrations in winter, in agreement with the findings of other authors (Titto et al, 2013). Frank et al (2003) observed increased baseline concentrations of the stress-related hormones ACTH and cortisol in response to brief exposure (i.e., 5 d) of pigs to cold.…”
Section: Resultssupporting
confidence: 93%
“…The difference in cortisol (Table 3) was significantly (p<0.05) lower in treatment group (24.33±1.84 ng/ml) in comparison to control (33.04±0.27 ng/ml) during winter while the difference was nonsignificant in spring in both control (15.63±0.48 ng/ml) and treatment (13.90±0.38 ng/ ml) group of animals. The present study found the highest cortisol concentrations in winter, in agreement with the findings of other authors (Titto et al, 2013). Frank et al (2003) observed increased baseline concentrations of the stress-related hormones ACTH and cortisol in response to brief exposure (i.e., 5 d) of pigs to cold.…”
Section: Resultssupporting
confidence: 93%
“…The inter-assay coefficient of variances (CVs) were 9.25% and 11.4% for CORT and IGF-I, respectively, and the intra-assay CVs were 12.1% and 12.9% for CORT and IGF-I, respectively. The kits were validated for cattle by demonstrating parallelism between standard concentrations and serially diluted samples curves (Pauletti et al 2005;Titto et al 2013).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…La même différence a été rapportée chez la vache (Titto et al, 2013), la chèvre (Alila-Johansson et al, 2003) et l'homme (Hadlow et al, 2014). Le dromadaire possède une activité sexuelle saisonnière stimulée par les jours décroissants de la saison d'hiver (El Khasmi et al, 2011).…”
Section: Analyses Statistiquesunclassified